The Relationship between Traumatic Experiences, the Prevalence of Social Anxiety and Insecure Attachment among University Students - Arijina, Aishwenee A.P.; Wenzhong, Wu; Jingyi, Lu; Keat, Ooi Boon (International Journal of Statistics in Medical Research, 2024)
University students face unique challenges and are considered a vulnerable population, making it crucial to understand the impact of trauma on their mental health. This study aimed to investigate the associations between traumatic experiences, the prevalence of social anxiety, and insecure attachment among MSU students. The present study adopted a quantitative research approach using the Trauma Screening Questionnaire (TSQ), the DSM-5 Severity Rating of Social Anxiety Disorder (SAD-D), moreover, for the purpose of assessing PTSD, the Vulnerable Attachment Styles Questionnaire (VASQ), Social Anxiety Disorder Severity, and Insecure Attachment, respectively. A total of 406 respondents participated in the research. Through descriptive analysis, data were collected using three different assessments, revealing that 67% of the students were identified as having a high risk of post-traumatic stress disorder (PTSD), while 6.9% experienced severe social anxiety, which was relatively low compared to the total number. Additionally, 87% of the students displayed a high level of insecure attachment. In order to test the research hypotheses, Pearson correlation analysis, linear regression analysis and path analysis were conducted in this study. The study’s findings demonstrated that there was a significant correlation between traumatic experiences and insecure attachment and a non-significant correlation between traumatic experiences and social anxiety. Additionally, traumatic experiences had a significant positive effect on insecure attachment but did not significantly affect social anxiety. Lastly, traumatic experiences did not significantly affect insecure attachment through social anxiety or traumatic experiences through social anxiety.